Protein folding and interactions revealed by mass spectrometry. - Last, A; Robinson, C (1999)
Mass spectrometry is capable of examining very large, dynamic proteins and this ability, coupled with its relatively high throughput and low sample requirements, is reflected by its increasing importance for the characterisation of protein structure. Recent developments in mass spectrometry, in particular the refinement of the electrospray process and its coupling with time-of-flight mass analysis, mean that it is poised to contribute not only as a complementary tool but also with a defined role in many areas of chemical biology.